Pengaruh Asupan Asam Folat Maternal terhadap kejadian Neural Tube Defect - Arina Muti Amaliah; Ratna Dewi PS (CV. Jasa Sukses Abadi, 2021)
Neural tube defects (NTDs) are common complex congenital malformations resulting from failure of the neural tube closure during embryogenesis. Human NTDs are multifactorial, with contributions from both genetic and environmental factors. The genetic basis is not yet well understood, but several nongenetic risk factors have been identified as have possibilities for prevention by maternal folic acid supplementation. Congenital abnormalities included in NTD include anencephaly, encephalocele, cranial meningocele, myelomeningocele, spinal meningocele, lipomeningocele, spina bifida, and several other brain defects. Spina bifida and anencephaly are the two most common forms of NTD. The incidence of NTD can be caused by several risk factors such as nutritional status, prevalence of obesity and diabetes, use of folic acid supplements and / or fortification, presence of toxicity in the environment, and different genetic predispositions between ethnic groups. The genetic basis is not well understood, but several non-genetic risk factors have been identified as likely to be prevented by maternal folic acid supplementation. The incidence of NTD can be reduced if women consume a folic acid supplement before and during the early weeks of pregnancy.Folate is involved in the methylation process of homocysteine ​​and cytosine. It also contributes to the synthesis of purines and pyrimidines. As a result, a lack of folate causes an inability to properly build proteins and DNA and also changes the expression of some genes. Although the role of folate in reducing the risk of NTDs is unknown, women of reproductive age are encouraged to include folate supplements in their diets.